1999
DOI: 10.1007/pl00013906
|View full text |Cite
|
Sign up to set email alerts
|

A Spaceflight Experiment for the Study of Gravimorphogenesis and Hydrotropism in Cucumber Seedlings

Abstract: Seedlings of Cucurbitaceae plants form a protuberance, termed peg, on the transition zone between hypocotyl and root. Our spaceflight experiment verified that the lateral positioning of a peg in cucumber seedlings is modified by gravity. It has been suggested that auxin plays an important role in the gravity controlled positioning of a peg on the ground. Furthermore, cucumber seedlings grown in microgravity developed a number of the lateral roots that grew towards the water containing substrate in the culture … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
31
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 13 publications
1
31
0
Order By: Relevance
“…On the other hand, rice coleoptiles bended adaxial direction toward the caryopsis (Hoson et al, 1999). Arabidopsis hypocotyls elongated in various directions (Hoson et al, 1999), and cucumber hypocotyls elongated straight in predetermined direction (Takahashi et al, 1999). In the present study, we showed that azuki bean epicotyls bended abaxial direction (Fig.…”
Section: Resultssupporting
confidence: 58%
“…On the other hand, rice coleoptiles bended adaxial direction toward the caryopsis (Hoson et al, 1999). Arabidopsis hypocotyls elongated in various directions (Hoson et al, 1999), and cucumber hypocotyls elongated straight in predetermined direction (Takahashi et al, 1999). In the present study, we showed that azuki bean epicotyls bended abaxial direction (Fig.…”
Section: Resultssupporting
confidence: 58%
“…When the gravitropic response is eliminated by mutation or clinorotation, the hydrotropic response can be detected, suggesting that the gravitropic response on Earth interferes with hydrotropism (Takahashi 1997a). In experiments carried out under low gravity conditions in space, we recently showed that the lateral roots of cucumber seedlings grew toward the wet substrate used as the seed-holding material and water source (Takahashi et al 1999. It was unusual to see lateral roots growing toward the shoot and deviating only 20-50° from the elongating axis of the primary roots.…”
Section: Introductionmentioning
confidence: 99%
“…On earth, lateral roots grow diagravitropically or plagiogravitropically, deviating greater than 90° from the axis of the primary roots that grow downward. Because of these results, we have proposed that positive hydrotropism controls the growth direction of the lateral roots under conditions of microgravity because the same response occurs during clinorotation under conditions of normal gravity (Takahashi et al 1999). The moisture gradient in the experimental chamber in experiments carried out in space was not measured; but, a relatively strong moisture gradient was probably maintained because the water-containing seed-holding material was placed at one end of the container in the absence of convection.…”
Section: Introductionmentioning
confidence: 99%
“…The most commonly used varieties are the one-axis slowrotating (1-4 rpm) clinostat and the two-axis or 3D clinostat, which also is termed the random positioning machine (16,17). In fact, hydrotropism in roots was more readily apparent when pea and cucumber seedlings were grown on a rotating clinostat (18,19), and the study by Kobayashi et al (4) used a clinostat to optimize the hydrotropic response in Arabidopsis seedlings.…”
mentioning
confidence: 99%
“…This concept has worked well in terms of phototropism, which can be stronger in microgravity compared with ground conditions (20,21). In fact, in the only available microgravity study, Takahashi and coworkers (19) found that in their space experiments with cucumber seedlings, lateral roots exhibited a positive hydrotropic response (not apparent on the ground) that was stronger in those roots closer to the wet substrate.…”
mentioning
confidence: 99%